Leadership behaviour on job satisfaction in Malaysian national secondary schools: Motivation and hygiene satisfaction - Siaw, Yan Li; Hassan, Dana (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
Inter-relationship between the principal and his/her teachers is vital in ensuring the success in school performance. Principal leadership behaviour is attributed to teachers’ job satisfaction thus may directly or indirectly, influence the achievement of school when striving for a goal or vision. The present study aims to determine the influence of principals’ leadership behaviour on teachers’ job satisfaction from the perception of a group of selected secondary schools teacher. Quantitative approach was used and questionnaires were distributed to 301 teachers for data collection. Descriptive and inferential analyses were used to analyse the data collected. Two instruments were utilized namely, (1) Leadership Behaviour Questionnaire and; (2) Teacher Job Satisfaction Questionnaire. The findings indicate that there is a significant correlation between principal leadership with teacher job satisfaction. This study also reports that the supportive and achievement-oriented leadership style influence teachers’ job statisfaction and contributed it to 30.7%. Our findings indicate that supportive leadership contributed more to the teachers’ job satisfaction compared to the achievement-oriented leadership style. This study confirms the importance of leadership behaviour on teachers’ job satisfaction. Generally, supportive and achievement-oriented leadership are the primary contributors to the satisfaction of the subordinate.